MERLOT: BELAJAR MUSIK DI ERA DIGITAL - Hidayatullah, Riyan (Journal of Music Science, Technology, and Industry, 2020)
This article is a literature review on MERLOT (Multimedia Education Resources for Online Learning and Teaching), an open-source multimedia-based learning resource for asynchronous music learning needs. Conventional music learning methods that deal with practical activities and theory classes. This activity is usually done in a classical or private class. In addition to general problems in music pedagogy and psychology, access to music materials in the form of music theory, music forms, and music literature is a problem that is specifically for music teachers in Indonesia. Access and publishing of music books are still minimal. These kinds of stuff carry out music teachers with non-music educational backgrounds to arrange music materials systematically, find out credible music learning resources, the latest issues about music learning and digital tools that can be used for online music courses. Various pieces of literature show that MERLOT is contributing to information literacy, digital, and supporting the learning of music nowadays.